Soya-cerebroside reduces IL-1β-induced MMP-1 production in chondrocytes and inhibits cartilage degradation: implications for the treatment of osteoarthritis. Issue 1 (1st January 2019) - Liu, Shan-Chi; Tsai, Chun-Hao; Wu, Tung-Ying; Tsai, Chang-Hai; Tsai, Fuu-Jen; Chung, Jing-Gung; Huang, Chih-Yang; Yang, Jai-Sing; Hsu, Yuan-Man; Yin, Mei-Chin; Wu, Yang-Chang; Tang, Chih-Hsin
ABSTRACT: Osteoarthritis (OA) commonly affects the synovial joint and is characterized by degradation of articular cartilage, which is largely mobilized by increased matrix metalloproteinase (MMP) activity. Soya-cerebroside, an extract of Cordyceps militaris, inhibits inflammatory cytokine production and monocyte migration in human synovial fibroblasts, although its effects are uncertain on MMP expression in chondrocytes and cartilage degradation. In this study, soya-cerebroside antagonized interleukin 1 beta (IL-1β)-induced MMP-1 production in chondrocytes, without cytotoxic effects. Functional genomic data confirm high levels of MMP-1 expression in OA tissue compared with normal tissue. Soya-cerebroside reduced MMP-1 expression via the focal adhesion kinase (FAK), mitogen-activated protein kinase (MEK), extracellular signal-regulated kinase (ERK) and AP-1 signalling pathways. In addition, soya-cerebroside suppressed IL-1β-promoted MMP-1 expression and cartilage degradation in animal models. Our report is the first to reveal that soya-cerebroside reduces MMP-1 production in chondrocytes and protects cartilage degradation through the FAK, MEK, ERK, and AP-1 signalling cascade.